Niveles De Motivación Y Las Competencias Laborales Específicas De Los Trabajadores A Distancia - Keith Polanco-Rico; J. Gerardo Reyes-López; Myrna I. García-Bencomo; Pedro J. Martínez-Ramos; María del Carmen Gutiérrez-Diez (European Scientific Journal, ESJ, 2017)
The aim of this study was to determine the relationship between motivation and specific job skills of teleworkers. The methodology was applied, descriptive and correlational. The study was hypothetical deductive, non experimental, transactional and quantitative. The sampling was non probabilistic by quotas, was included telecommuters from different companies that use this type of work, located in the interior of Mexico, USA and Canada. The sample size was 27 teleworkers. A questionnaire of 52 questions was used as a measuring tool. The data analysis was descriptive and chi square test was used to identify the relationship of the independent variable motivation with the dependent variable specific job skills of teleworkers. The main results showed that motivation is high and teleworkers have a high development in most of their job skills. Also among the most outstanding results it was found that the variable motivation in the three indicators analyzed: the need for existence, value and growth, have a closer relationship with labor competition autonomy, than the rest of labor skills analyzed.